(untitled) - Robert M freedom...[et al.] (Armonk, New York, 1997)
The book provides a comprehensive overview of angiocardiography in congenital heart disease and the clinical and management implications based on these images
Keywords: angiocardiography - in infancy and childhood,heart diseases - in infancy and childhood,heart diseases - radiography